Zadovoljstvo bolnikov - Kersnik, Janko (Medicinski razgledi, 1999)
Patient statisfaction is an important aim pursued by medical care. It is determined by the quality of communication, interpersonal relationships and delivery of services. The wey the patient feels about the medical services received is an invaluable indicator of the quality of care, which can be used for setting priorities for quality improvement.
Keywords: družinska medicina; Patient satisfaction; Quality of health care; bolniki; Questionnaires; zdravstvena nega